Motility in the epsilon-proteobacteria - Beeby,M (Current Opinion in Microbiology, 2015)
The epsilon-proteobacteria are a widespread group of flagellated bacteria frequently associated with either animal digestive tracts or hydrothermal vents, with well-studied examples in the human pathogens of Helicobacter and Campylobacter genera. Flagellated motility is important to both pathogens and hydrothermal vent members, and a number of curious differences between the epsilon-proteobacterial and enteric bacterial motility paradigms make them worthy of further study. The epsilon-proteobacteria have evolved to swim at high speed and through viscous media that immobilize enterics, a phenotype that may be accounted for by the molecular architecture of the unusually large epsilon-proteobacterial flagellar motor. This review summarizes what is known about epsilon-proteobacterial motility and focuses on a number of recent discoveries that rationalize the differences with enteric flagellar motility.